(3GdSjGSI aj Yde GdaQGSIs - (3TjN GdQHhI , CHh YHO Gddg eMeO Hf CHj WGdH GdCfUGQj GdUhaj GdOeTbj, TjN GdQHhg (B/ (3TjN MWjf,J (B727 (3g` s
(3ChdgG (B:s
(3GeG HYO agPg QSGdI eTJedI Yd eYGbO LeI ef Yde GdaQGSI dGLd GdSjGSI s
(3BNQgG (B:s
(3hHJeGegG Je gPG GdJCdja ai GdaQGSI HMeO Gddg JYGdi hYhfg hMSf Jhajbg hGdMeO ddg s
(3jdMX Cfg jhLO ai gPG GdagQS KdGK QSGFd ai GdaQGSI ddaGQGHj hdTjN GdQHhI hddaNQ GdQGRjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B94s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B130 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B161 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B142 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI QVG QGeHhQ HGdgfO (B(3451) s
Keywords: (3GdaQGSIs